Analisis Keterpaduan Muatan Kurikulum Merdeka Dalam Pembelajaran Pendidikan Agama Islam - Anita Kusma Dewi; Nur Jannah (GHAITSA : Islamic Education Journal, 2025)
The Independent Curriculum offers greater flexibility in learning. This research analyzes the extent to which this flexibility is utilized to integrate Islamic Religious Education (PAI) content with other subjects. Through case studies in several schools, this research found that the implementation of the Independent Curriculum in PAI still faces challenges, such as lack of resources, varying teacher competencies, and resistance to change. However, there are also good practices that show the potential for deeper PAI integration. The implementation of the Independent Curriculum has provided new flexibility in learning Islamic Religious Education (PAI). This research aims to identify the challenges and potential of integrating PAI content in the context of this more flexible curriculum. Through the library method, at SMPN 2 Kabawetan, it was found that teachers still faced obstacles in developing problem-based project materials. However, there is great potential in using technology for interactive learning. This research suggests the need for more intensive teacher training and the development of diverse learning resources